2018
DOI: 10.1155/2018/4686531
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Coordination under Inventory Inaccuracy with RFID Technology

Abstract: In this paper we consider a two-echelon supply chain under price-dependent demand market and we use RFID to eliminate the effect of inventory inaccuracy. Models are built to evaluate the economic viability and coordination conditions. We analyze two scenarios in which the supply chain is defined, the integrated one and the decentralized one, respectively. For the integrated, we compare the different supply chain revenue with and without RFID technology and then determine the optimal inventory decisions. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Using fuzzy and novel robust optimization as a data-driven approach is advantageous for a risk-averse decision-maker in the recent decade. Eventually, we suggest equipping all SC with novel technology such as Internet of ings (IoT) and RFID [35] to increase SC's viability.…”
Section: Discussionmentioning
confidence: 99%
“…Using fuzzy and novel robust optimization as a data-driven approach is advantageous for a risk-averse decision-maker in the recent decade. Eventually, we suggest equipping all SC with novel technology such as Internet of ings (IoT) and RFID [35] to increase SC's viability.…”
Section: Discussionmentioning
confidence: 99%
“…The leading causes of inaccuracy in inventory cited by literature are human errors in the execution of tasks (such as receiving, picking, shipping, delivery, and scanning) and incorrect records (Barratt et al, 2018; Production, 33, e20220077, 2023 | DOI: 10.1590/0103-6513.20220077 4/16 Best et al, 2022;Chuang & Oliva, 2015;Drohomeretski & Favaretto, 2013;Lei et al, 2018;Rekik et al, 2019a, b;Sarac et al, 2010), theft (Qin et al, 2017;Su et al, 2021;Waller et al, 2006) obsolescence (Kang & Gershwin, 2005), incorrect location (Brown et al, 2001;Raman et al, 2001), lack of training (Brown et al, 2001), long time between physical inventories (DeHoratius & Raman, 2008), damage (Rekik et al, 2019b), shrinkage (Chuang & Oliva, 2015;Lei et al, 2018;Wang et al, 2016), lack of clear procedures (Raman et al, 2001), low employee remuneration or motivation (DeHoratius & Raman, 2008), inaccessible inventory (Lei et al, 2018), lack of CC (Brown et al, 2001). Best et al (2022) demonstrated that items' misplacement rate was one of the main drivers of positive IRI.…”
Section: Causes and Solutions For Inventory Record Inaccuracymentioning
confidence: 99%
“…There is also a focus on specific SCs related to particular industries such as food, electronic equipment manufacturing with a focus on how RFID combined with other most advanced tools from IoT and BCT can improve profitability and the return on investment. A historiographical analysis (Aria and Cuccurullo, 2017) of direct citation in Figures 10a and b shows are three emerging trends: (1) SC performance improvement and inaccuracy mitigation using RFID (Bottani et al , 2017; Lei et al , 2018; Cui et al , 2017; Biswal et al , 2018; Zhang et al , 2018 ; Rao et al , 2019; Drakaki and Tzionas, 2019; Chen, 2020; Zhang and Wang, 2020); (2) Security and surveillance in SC (De Virgilio and Milicchio, 2016; Maleki et al , 2017; Sidorov et al , 2019); (3) BCT and its application in SC (Tian, 2016; Mondal et al , 2019; Sidorov et al , 2019; van Hoek, 2019; Hilt et al , 2018); (4) IOT in SC (Ben-Daya et al , 2019; Tian, 2017; Manavalan and Jayakrishna, 2019; Mondal et al , 2019; Zelbst et al , 2020; Yang et al , 2018; Podduturi et al , 2019); Food SC related to agriculture (Hilt et al , 2018; Juan and Shiling, 2017). Based on these insights, we have highlighted some potential research suggestions in Table 8.…”
Section: Emerging Trends and Implications Using Content Analysismentioning
confidence: 99%